Relationships between employment status with self-perceived mental and physical health in Canada - Anson Kwok Choi Li; Behdin Nowrouzi-Kia (AIMS Press, 2024)
Background: The annual cost of mental illnesses in Canada is estimated to be ＄50 billion. Research from other countries have suggested that employment status is associated with mental and physical health. Within the Canadian context, there is a dearth of research on the relationship between employment and mental health. Objective: To explore the relationships between age, gender, income, and employment status on mental and physical health. Methods: The 2021 Canadian Digital Health Survey dataset was used for this study. Data records, which included responses for the questions on age, gender, income, employment status, mental, and physical health, were used in the analysis. Ordinal logistics regression was applied to investigate the associations that may exist between mental and physical health with the various sociodemographic factors. Descriptive statistics were also provided for the data. Results: The total sample size included in the analysis was 10,630. When compared to respondents who had full-time employment, those who were unemployed were more likely to have lower self-perceived mental health (OR: 1.91; 95% CI: 1.55-2.34). Retired respondents were less likely to have worse mental health than respondents who were employed full-time (OR: 0.78; 95% CI: 0.68-0.90). Self-perceived physical health was more likely to be lower for those who were unemployed (OR: 1.74; 95% CI: 1.41-2.14) or retired (OR: 1.28; 95% CI: 1.12-1.48) when compared to respondents employed full-time. The likelihood of worsening mental and physical health was also found to be associated with age, gender, and income. Conclusion: Our findings support the evidence that different factors contribute to worsening mental and physical health. Full-time employment may confer some protective effects or attributes leading to an increased likelihood of having improved mental health compared to those who are unemployed. Understanding the complex relationships on how various factors impact mental health will help better inform policymakers, clinicians, and other stakeholders on how to allocate its limited resources.